A joint market temporal rolling bidding strategy for virtual power plants in the wholesale market - Mao, Tian; Lin, Hanyang; Cheng, Renli; Li, Jiangnan; Zhou, Baorong; Zhao, Wenmeng; Wang, Tao (Frontiers in Energy Research, 2024)
Massive and diversified distributed energy resources (DERs) have great potential for improving the flexibility of power system operations. However, given the wide distribution, small capacity, and variable ownership subject characteristics of DERs, virtual power plants (VPPs) are suitable for aggregating the flexible DERs for participation in the wholesale energy market. Extant studies have focused on obtaining bidding strategies in multiple electricity markets. However, there are shortcomings in the relevant market mechanisms and temporal relationships for participating in energy and ancillary service markets. This work proposes a joint market temporal rolling bidding strategy for VPPs in the wholesale market based on real unified electricity market mechanisms in the southern region of China. Accordingly, the proposed method enhances the market-oriented operational profits of VPPs.